SPE Annual Technical Conference and Exhibition 1981
DOI: 10.2118/10101-ms
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Water-Soluble Polymers on High Surface Area Clays

Abstract: The adsorption of water-soluble polymers, predominately of the polysaccharide type, on attapulgite, bentonite and berea sand/bentonite (15 wt,%) agglomerated substrates and on deflocculated bentonite suspensions has been conducted. In the agglomerated substrate studies the molecular weight of derivatied polysaccharides was an important factor; the lower the molecular weight the greater the adsorption. Molecular weight was not important in adsorption on deflocculated bentonite substrates. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The deflocculated system may increase the adsorption. 45,49,50 3.3. Effect of Clay Mineral Percentage on Aerosol-OT Dynamic Adsorption.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The deflocculated system may increase the adsorption. 45,49,50 3.3. Effect of Clay Mineral Percentage on Aerosol-OT Dynamic Adsorption.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the molecular weight of alkali lignin prevents its flow in the internal surface area. 49 Overall, lignin covers the solid surface, thereby minimizing the loss of the surfactant. The alkali lignin covers the surface and establishes the hydrogen bond to prevent Aerosol-OT adsorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When permeability is low, the ratio of pore-wall surface to pore volume is high, corresponding to higher polymer adsorption. Consistently, polymer hydrodynamic retention-typically modeled through an adsorption isotherm-is known to increase with increasing pore velocity [36], and therefore scales with the inverse of permeability [32,37]. Ahmed et al [38], found that polymer adsorption generally decreases with increasing viscosity in rocks with high clay content.…”
Section: Factors That Impact Performance In Polymer Floodingmentioning
confidence: 94%
“…Mechanical degradation was simulated by shearing the polymer solution using a waring blender at different speeds, that is, 3500, 7000, and 10 500 rpm for 20 s.…”
Section: Methodsmentioning
confidence: 99%